Discussion on Modern Knowledge of Negative Impacts in Psychotherapy and Suggestions for Further Studies - Quratulain Haider, Kashaf Shamrez, Ansab Jalil, Attaullah Bangulzai, Naseem Khan, Syed Aqeel Akbar Shah Gillani (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Psychotherapy has been shown to reduce mental suffering and enhance quality of care, but little is recognized around its possible adverse impact as well as how to determine their frequency. To introduce a discussion on modern knowledge of negative impacts in psychotherapy and suggestions for further studies directions. Methods: An unidentified survey should be sent to a small elite team of researchers, who were then evaluated using just a framework known as strengths, weak points, possibilities, and risks. Results: The scientists believe that there has been a growing understanding of detrimental consequences in psychotherapy in recent times, but they also explain a few of the unsettled problems pertaining their description, evaluation, and disclosing. Qualitative methods and naturalism styles are viewed as essential to undertake, spite of the fact that a number of barriers to would use such techniques have been recognized. Conclusion: Psychotherapy’s adverse consequences are multidimensional, necessitating positively evaluates in order for them to be controlled and disclosed in study designs and routine procedures.